Coaching and Mentoring untuk Meningkatkan Kompetensi Guru dalam Menerapkan Model Problem Based Learning (PBL) pada Muatan Pelajaran IPA Sekolah Dasar - Umabiinatun Umabiinatun (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This School Action Research aims to find out the coaching and mentoring steps taken by the school principal to increase teacher competence in implementing the PBL model at SD Negeri 1 Kulwaru. This School Action Research was carried out by following the model developed by Kemmis and Mc Taggart, through four stages: planning activities, carrying out activities, observing, and reflecting on what happened and was done. The implementation stage of the action consists of three meetings. The first meeting agreed on a schedule and procedure for activities between the principal and the teacher. In the second meeting, the Principal reviewed the lesson plan prepared by the teacher and observed the implementation of learning using the PBL model. The third meeting of the Principal carried out coaching and mentoring of the learning carried out. The stages of coaching and mentoring at Kulwaru 1 Public Elementary School are carried out by assisting teachers in carrying out their duties through mentoring, directing, providing advice, support, encouragement, guidance, and providing feedback in interpersonal relationships for teachers. Research data shows that coaching and mentoring can improve teachers' abilities to use the PBL model in the science learning process, including preparing lesson plans and carrying out learning. There was an increase in the teacher's ability to prepare lesson plans from the Pre-Cycle mean score of 76.52 (Enough); in Cycle I it reached 79.56 (Enough); and in Cycle II obtained 87.22 (Good). Meanwhile, the teacher's ability to carry out science learning using the PBL model, from the Pre Cycle mean value of 77.00 (Enough); in Cycle I it reached 79.93 (Enough); and in Cycle II obtained 85.53 (Good).